Efficacy evaluation of contemporary and alternative medicine in managing diabetes mellitus: A review - E. G. Moke; Peace Onyilo; Emuesiri Umukoro; Ejiro Awhin; Benneth Ben-Azu; Jerome Asiwe; Sinodukoo Okafo; Jacinta Apitikori-Owumi; Tochukwu Nduka; Fumnanya Emeka; Nkechi Isibor (Orapuh Journal)
Diabetes mellitus poses a significant global health burden, and achieving optimal glycemic control is crucial in preventing complications. Traditional medicine, rooted in cultural beliefs and practices, has been used for centuries to manage diabetes mellitus. In recent years, contemporary medicine, including pharmaceutical approaches, has gained prominence in diabetes management. This review aims to evaluate the efficacy of contemporary and alternative medicine in managing diabetes mellitus. Evidence-based research is essential to validate the efficacy of alternative medicine and integrate it effectively with contemporary methods for comprehensive diabetes management. This review provides valuable insights into the current diabetes treatment landscape and outlines recommendations for future research and healthcare practices. A total of 107 relevant articles were reviewed, covering studies up to 2024, using search engines and databases such as PubMed, Scopus, Web of Science, and Google Scholar. Both contemporary and alternative medicines show promise in managing diabetes, with an integrated approach potentially offering optimal outcomes. However, further evaluation of the safety of these medicines is necessary, as this remains a limitation and an avenue for future studies.